Oral Health-related Quality of Life (OHRQoL) of Patients undergoing Micro-osteoperforations (MOPs) to Accelerate Orthodontic Space Closure/ Syed Bazli Alwi Syed Bakhtiar... [et al.] - Syed Bakhtiar, Syed Bazli Alwi; Norman, Noraina Hafizan; Abdul Ghani, Sarah Haniza; Md Sabri, Budi Aslinie (Faculty of Dentistry, 2017)
Objectives: To assess and compare the oral health-related quality of life (OHRQoL) of orthodontic patients who had and had not undergone micro-osteoperforations (MOPs) during orthodontic space closure. Methods: 27 orthodontic patients with fixed appliance who are undergoing orthodontic space closure with Niti coil springs were given the validated short version of the Oral Health Impact Profile (Malaysia) Questionnaire (S-OHIP) which was available in both Bahasa Melayu and English, containing 14 items. 17 patients underwent MOPs (MOP group) while 10 patients did not (control). Additive scores (ADD) were calculated by summing the response codes for the 14 items and simple count scores (SC) were calculated by a count of the number of items reported as occurring 'quite often' and 'very often'. Results: A total of 24 patients responded to the questionnaire, with a response rate of 88.9%, and they comprised of 79.2% females and 20.8% males. There is no significant difference in the mean ADD (p = 0.347) and mean SC (p = 0.446) across both groups. Conclusions: The reported oral health-related quality of life is similar for orthodontic patients who did and did not undergo MOPs.